Sorafenib in a hepatocellular carcinoma patient with end‐stage renal failure: A pharmacokinetic study. Issue 6 (31st May 2013) - Ishii, Takamichi; Hatano, Etsuro; Taura, Kojiro; Mizuno, Tomoyuki; Kawai, Tomoki; Fukudo, Masahide; Katsura, Toshiya; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> The efficacy of sorafenib against hepatocellular carcinoma (HCC) has been extensively reported. However, there is little information available about the use of sorafenib for HCC patients with end‐stage renal failure. We herein report the safe introduction of sorafenib therapy for a HCC patient on hemodialysis. A 63‐year‐old man had received multidisciplinary treatments, including transarterial chemoembolization (TACE) and radiofrequency ablation, for HCC since 1996, and had been undergoing hemodialysis since 2005. He also underwent TACE for multiple liver recurrence of HCC in 2011. Sorafenib therapy (200 mg/day) started 8 days after the TACE. The pharmacokinetic parameters of sorafenib and its active metabolite, M‐2, were within the reference levels observed in patients with normal renal function 8 and 9 days after the initiation of sorafenib. The dose of sorafenib was reduced to 200 mg every other day on day 154 due to hypertension and general fatigue. Because of the progression of disease after 5 months, sorafenib was withdrawn on day 180. He was admitted to the emergency department because of a high fever during hemodialysis on day 201, and died of septic shock induced by Staphylococcus lugdunensis on day 203. Sorafenib was well tolerated at an initial dose of 200 mg/day for a HCC patient undergoing hemodialysis, thus indicating that renal failure is not necessarily a contraindication for sorafenib therapy.